Manajemen Sekolah Menengah Atas Swasta dalam Meningkatkan Mutu Sekolah di Kota Lubuklinggau - Ahmad Gawdy Prananosa; Marianita Marianita; Rudi Erwandi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study was to determine the management of private high schools in improving school quality. This study used a qualitative approach with a phenomenological method. The subjects of the study consisted of the Principal, Teachers' Council, and School Staff. Data collection techniques; interviews, documentation, and observation. Using the Miles & Huberman data analysis technique, namely interactive model analysis. The results of the study, educators and education personnel, were carried out through selective recruitment, ongoing training, competency development, and routine performance evaluations. Students formed OSIS, extracurricular clubs, and coaching teams to support student activities. Facilities and infrastructure, namely compiling a facility management team, setting a maintenance schedule, recording needs. Finance, namely optimizing the use of existing facilities, carrying out routine maintenance, and ensuring the feasibility of facilities to support the learning process. Facilities and infrastructure through periodic audits, checking the feasibility of facilities, and collecting input from users for improvement and development. Conclusion, the management of private high schools in improving school quality consists of planning, organizing, implementing and evaluating schools which include; teaching and education personnel, students, facilities and infrastructure, finance, and curriculum. Keywords: Management, School Quality, Senior High School